STRATEGI RETENSI NASABAH DI BANK ACEH SYARIAH MELALUI PENINGKATAN KUALITAS PELAYANAN - Salihan Mustafa; Rila Maufira; Roezaini Sofi (Jurnal Ekonomi, Manajemen dan Akuntansi, 2026)
The increasing competition in the Islamic banking industry requires financial institutions not only to acquire new customers but also to focus on retaining existing ones. Customer retention plays a strategic role as it is directly linked to long-term relationships and the profitability of the bank. This study aims to examine the effect of service quality as well as satisfaction and trust on customer retention at Bank Aceh Syariah. The research adopts a quantitative approach with the method of multiple linear regression analysis. The sample consists of 286 respondents selected through purposive sampling, namely active customers with a minimum banking relationship of two years. Data were collected through a Likert-scale questionnaire and analyzed using statistical software. The findings indicate that service quality has a positive and significant effect on customer retention. Similarly, satisfaction and trust are proven to significantly influence customer retention. Simultaneously, both variables contribute significantly to customer retention, with a coefficient of determination (R²) of 0.520. This means that 52% of the variation in customer retention can be explained by the research model, while the remaining 48% is influenced by other factors beyond this study. These results emphasize the importance of enhancing service quality that complies with Sharia principles, accompanied by efforts to build satisfaction and trust. The practical implication suggests that consistent, transparent, and innovative service strategies are essential for Bank Aceh Syariah to sustain long-term customer loyalty